ROLE OF ARTIFICIAL INTELLIGENCE IN AGRICULTURE OF INDIA - M. Barad, Mahesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Integrating Artificial Intelligence (AI) in agriculture holds great promise for optimizing resource utilization, improving crop yields, and promoting sustainable practices. However, the responsible adoption of AI in agriculture is critical to addressing ethical challenges, ensuring Transparency and avoiding unintended negative consequences. The responsible adoption of AI in agriculture entails a conscientious and ethical approach to integrating AI into farming practices. This research explores Ethical concerns, Transparency and Sustainable resource management by proposing a novel ETS framework for the responsible adoption of AI in agriculture and a case study of its application to achieve this objective. This framework can be a helpful tool to maximize the benefits of technology while safeguarding ethical, transparent, and sustainable outcomes for all stakeholders and the environment.